“Las competencias comunicativas en el trabajo áulico en los docentes de Educación Inicial” - Casa Chango, Evelyn Yadira (2023)
This research project focuses on the topic of communicative competencies in classroom work in early education teachers, with the problem that there are deficiencies in communication between teachers and students, because they do not have training on different communicative competencies, for which the general objective of this research was to diagnose the communicative competencies in classroom work, through the application of methodological instruments in early education teachers in the Educational Unit “Coronel Germánico Ribadeneira Valencia”. This study was determined by the interpretative paradigm, which helped to discover the reality of the problem, through the qualitative approach that describes the qualities of the subject, its research modality was field and bibliographic, the type of research was exploratory and descriptive, the research method was focused on participatory action and the inductive method, the research instruments used were the interview guides, applied to the rector on the other hand to parents; The observation form was used to measure the level of knowledge that teachers have in relation to communicative competencies. The results of the application of the instruments were the following: the children presented gaps in their significant learning due to the lack of good communication and the lack of didactic and technological resources on the part of the teachers; to make up for this deficiency, a “methodological guide” was proposed for the teacher, for the reason that it is a process that aims to introduce communicative strategies.